2022
DOI: 10.3390/nu14194213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Very Low-Calorie Ketogenic Diet (VLCKD) on Changes in Handgrip Strength in Women with Obesity

Abstract: The preservation of muscle mass, which is positively associated with muscle strength, has been included among the benefits of ketogenic diets due to the synergistic effects exerted by the reduction in visceral adipose tissue and obesity-related pro-inflammatory status. The handgrip strength (HGS) test is widely used as a single indicator to represent overall muscle strength. The possible association of changes in HGS in patients with obesity during the consumption of a very low-calorie ketogenic diet (VLCKD) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…2 Short-term positive mechanisms of action of the ketogenic diet on energy metabolism and muscle mass adipose tissue and obesity-related pro-inflammatory status [98]. In fact, in their study, the authors showed that at the end of a 45-days VLCKD protocol, there was an increase in muscle strength (∆ + 17.4 ± 13.2%; p = 0.001) [98].…”
Section: Mechanisms Of Action Of the Ketogenic Diet On Energy Metabol...mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Short-term positive mechanisms of action of the ketogenic diet on energy metabolism and muscle mass adipose tissue and obesity-related pro-inflammatory status [98]. In fact, in their study, the authors showed that at the end of a 45-days VLCKD protocol, there was an increase in muscle strength (∆ + 17.4 ± 13.2%; p = 0.001) [98].…”
Section: Mechanisms Of Action Of the Ketogenic Diet On Energy Metabol...mentioning
confidence: 99%
“…According to Barrea et al, the preservation of muscle mass, which is positively associated with muscle strength, has been included among the benefits of VLCKD due to the synergistic effects exerted by the reduction in visceral Fig. 2 Short-term positive mechanisms of action of the ketogenic diet on energy metabolism and muscle mass adipose tissue and obesity-related pro-inflammatory status [98]. In fact, in their study, the authors showed that at the end of a 45-days VLCKD protocol, there was an increase in muscle strength (∆ + 17.4 ± 13.2%; p = 0.001) [98].…”
Section: Mechanisms Of Action Of the Ketogenic Diet On Energy Metabol...mentioning
confidence: 99%
“…Силу мышц измеряли с помощью силы хвата кисти, состав тела оценивали с помощью биоимпедансного анализа. В результате, наряду со значительным снижением массы тела и улучшением композиционного состава тела, отмечено увеличение силы хвата кисти [48]. Однако по сравнению с исследованием Camajani E. и соавт.…”
Section: профилактика и лечение соunclassified
“…The VLCKD provided a total daily energy intake < 800 kcal, with 13% carbohydrates (< 30 g/day); 43% protein (1.2-1.5 g/kg ideal body weight); 44% lipids (mainly from extra-virgin olive oil). According to the international recommendations, participants were prescribed a multi-vitamin and saline supplement (complex B vitamins, vitamins C and E, potassium, sodium, magnesium, calcium, and omega-3 fatty acids; PentaCal, Penta, s.r.l., Cuneo, Italy), as reported in previous studies [34][35][36]. In all participants, physical activity (at least 30 min/day aerobic exercise) was assessed using a YES/ NO response, as reported in previous studies [37][38][39].…”
Section: Nutritional Interventionmentioning
confidence: 99%